2000
DOI: 10.1073/pnas.250476497
|View full text |Cite
|
Sign up to set email alerts
|

The repertoire for pattern recognition of pathogens by the innate immune system is defined by cooperation between Toll-like receptors

Abstract: Toll-like receptors (TLRs) have been shown to participate in the recognition of pathogens by the innate immune system, but it is not clear how a restricted family of receptors has the capacity to recognize the wide spectrum of TLR stimuli known to exist. We report here that two members of the TLR family, TLR2 and TLR6, together coordinate macrophage activation by Gram-positive bacteria and the yeast cellwall particle, zymosan. TLR6 and TLR2 both are recruited to the macrophage phagosome, where they recognize p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
1,374
2
21

Year Published

2001
2001
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,837 publications
(1,429 citation statements)
references
References 35 publications
32
1,374
2
21
Order By: Relevance
“…work has demonstrated that TLR2 is recruited to macrophage phagosomes containing either zymosan or IgG-opsonized sheep red blood cells [36,37], and similar to these observations, we also observed TLR2 enriched in P. aeruginosa endosome after 45 min of in vitro infection (Fig. 6B, i-iii).…”
Section: Mr Complexes With Tlr2 and Modulates Signaling Within Endosomessupporting
confidence: 89%
“…work has demonstrated that TLR2 is recruited to macrophage phagosomes containing either zymosan or IgG-opsonized sheep red blood cells [36,37], and similar to these observations, we also observed TLR2 enriched in P. aeruginosa endosome after 45 min of in vitro infection (Fig. 6B, i-iii).…”
Section: Mr Complexes With Tlr2 and Modulates Signaling Within Endosomessupporting
confidence: 89%
“…To investigate the receptors involved in NADPH oxidase activation, DC were stimulated with purified biglycan, glucan and Pam 3 CSK4, specific agonists of CD206, dectin-1 and TLR2, respectively [44][45][46]. We found that biglycan and Pam 3 CSK4, alone or in combination, did not activate ROS production (Fig.…”
Section: Dectin-1 Mediates Nadph Oxidase Activationmentioning
confidence: 88%
“…Based on our findings, it appears that in the presence of LPS contamination, activation of intracellular signaling pathways could involve interactions of the particle-associated LPS with LPS receptors on the cell surface [3,43,60]. In the absence of LPS contamination, adsorption and denaturation of serum proteins onto particle surfaces may function as ligands with LPS-like activity that could, in a similar fashion, interact with cell surface receptors to induce cell response.…”
Section: Discussionmentioning
confidence: 99%